2024
DOI: 10.3390/w16030466
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Solutions for Water Treatment: Unveiling the Potential of Polyoxazoline Polymer Activated Carbon Composite for Efficient Elimination of Lead Ions

Abdelfattah Amari,
Mohamed Boujelbene,
Fatima Moayad Sami
et al.

Abstract: Heavy metal pollution is a global problem that necessitates the development of innovative and environmentally friendly water treatment technologies. Polyoxazoline polymers, known for their biocompatibility, are explored for lead ion removal in water treatment. Poly 2-Methoxycarbonylpropyl-2-oxazoline is integrated into activated carbon via in situ polymer growth, optimizing loading through live polymerization. This study investigates intricate interactions between lead ions and functional groups, such as amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Until now, numerous researchers have experimented with various approaches to purify water resources, including chemical precipitation, membrane separation, biological treatment, and adsorption 27 30 . Among the diverse methods for removing contaminants, adsorption is notable for its cost-effectiveness, straightforward operation, selectivity, and high efficiency 31 33 . For instance, many researchers have shown that membrane filtration suffer from a drawback of fouling and costly process 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Until now, numerous researchers have experimented with various approaches to purify water resources, including chemical precipitation, membrane separation, biological treatment, and adsorption 27 30 . Among the diverse methods for removing contaminants, adsorption is notable for its cost-effectiveness, straightforward operation, selectivity, and high efficiency 31 33 . For instance, many researchers have shown that membrane filtration suffer from a drawback of fouling and costly process 34 .…”
Section: Introductionmentioning
confidence: 99%